1998
DOI: 10.1016/s0261-2194(97)00117-8
|View full text |Cite
|
Sign up to set email alerts
|

Biology and management of Melanagromyza obtusa (Malloch) (Diptera:Agromyzidae)

Abstract: Melunagromyza obtusa (Malloch) (Diptera:Agromyzidae), the pigeonpea pod fly, is a key pest of pigeonpea [Cajunus cajun (L.) Millsp.] throughout south and southeast Asia. Females deposit eggs in the green pods of pigeonpea and other host plants, and the developing larva feeds on and destroys the unripe seed. Substantial yield losses have been attributed to this pest in several countries. Pest management strategies for the pigeonpea pod fly have emphasized chemical control and host-plant resistance. This paper r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…The other most damaging insect, which has been identified as one of the most important yield reducing factors, is the pod fly (Melanagromyza obtusa Malloch) [10], causing an annual loss of US $256 million annually [6]. It causes an average of 34.5% pod damage, which in turn results in 29.8% grain loss [11].…”
Section: Introductionmentioning
confidence: 99%
“…The other most damaging insect, which has been identified as one of the most important yield reducing factors, is the pod fly (Melanagromyza obtusa Malloch) [10], causing an annual loss of US $256 million annually [6]. It causes an average of 34.5% pod damage, which in turn results in 29.8% grain loss [11].…”
Section: Introductionmentioning
confidence: 99%
“…The predators and parasitods have been summarized for the key insects pest in pigeonpea such as Helicoverpa armigera (Sithanantham et al, 2005), Maruca vitrata (Sharma et al, 1998), Melanoagromy zaobtusa (Shanower et al, 1998). Around 97 species of parasitods have been recorded on different insect pest occurring in pigeon pea (Rabindra et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Distribution: Bangladesh: Chittagong, CU campus; Hathazari; Cox's Bazar, St. Martin's Island (present work); India (Yadav & Yadav 2013); Myanmar, Nepal, Pakistan, Philippines, Thailand, Vietnam, China, Taiwan, Indonesia, Malaya, Sri Lanka, New guinea and Japan (Delfino & Hardy 1967;Shanower et al 1998Shanower et al , 1999Spencer 1973) and Australia (Spencer 1999 (Rahman 1991;Mia 1998;Prodhan et al 2000). In the present study the leafminers L. chinensis, L. sativae, M. obtuse and O. phaseoli were reared from different plant hosts which are not recorded earlier.…”
mentioning
confidence: 80%
“…Spencer (1990) noted that M. obtusa is not host-specific. In addition Shanower et al (1998) reported five host plant genera in the legume family as hosts: Cajanus (e.g., Arhar), Dunbaria (e.g., Heyne's Pegionpea); Flemingia (e.g., Slender Fremingia), Rhynchosia (e.g., Himalayan Snoutbean), and Tephrosia (e.g., White Hoary Pea). This pest was reared from L. purpureus (Country Bean), G. max (Soya Bean), P. aureus (Mung Bean) and V. unguiculata (Cowpea) in the present investigation.…”
mentioning
confidence: 99%